CHARACTERISTICS OF ROAD TRAFFIC ACCIDENTS BASED ON PUBLIC HOSPITAL SERVICES - Jéssica Rodolfo Campos; Eliane Regina Pereira do Nascimento; Patrícia Madalena Vieira Hermida; Sabrina Guterres da Silva Galetto; Maíra Antonello Rasia; Natyele Rippel Silveira (Universidade Federal do Paraná, 2018)
Objective: to characterize road traffic accidents based on the services provided in public reference hospitals of the state of Santa Catarina. Method: descriptive, quantitative research. Data of the accidents were collected from July to September 2015 through the use of a structured form. The sample consisted of 139 medical records of two emergency units. Descriptive statistics was applied in the analysis. Results: the accidents mainly involved men (n=112; 80.6%), aged from 20 to 29 years (n=53; 38.2%). There was a predominance of car/motorcycle accidents (n=44; 31.7%) on Fridays (n=27; 19.4%) in the evening (n=11; 7.9%). Lower limbs represented the most commonly body segment individually affected (n=49; 35.2%). In most accidents (n=95; 68.3%) the patient remained hospitalized for at least 24 hours. Conclusion: preventive measures for road traffic accidents should be especially focused on young men that use cars and motorcycles, with an emphasis on traffic control actions on the eve of weekends and actions promoting the use of safety equipment.